Kearifan Lokal Huma Betang sebagai Basis Pendidikan Moderasi Beragama di Perguruan Tinggi Islam - Muhammad Redha Anshari; Yusuf Wibisono; Imam Basofi; Syahmidi Syahmidi (Lembaga Yasin AlSys, 2025)
In Central Kalimantan, values of tolerance are deeply rooted in the local wisdom of the Dayak community through the Huma Betang philosophy, which not only represents the structure of a longhouse but also symbolizes communal life grounded in the principles of togetherness, deliberation, and respect for social and religious differences. This study aims to develop an effective model of religious tolerance based on the Huma Betang philosophy within the context of Islamic higher education, with a case study on the Islamic Religious Education (PAI) Study Program in Central Kalimantan. A mixed methods approach was employed, combining qualitative techniques through interviews and observations with a quantitative survey administered to 62 students. The findings reveal that the religious tolerance model in the PAI program is built on three core pillars: (1) integration of tolerance values into the academic curriculum, (2) application of dialogical and contextual teaching strategies by lecturers, and (3) reinforcement of academic culture through interfaith student activities. Quantitative data confirm that the majority of students demonstrate increased awareness and inclusive attitudes toward religious diversity. This study underscores that the internalization of tolerance values in Islamic higher education requires the active role of institutions and lecturers in fostering a moderate, contextual, and locally grounded learning ecosystem. The implications suggest that this model is not only relevant for shaping moderate student character but also contributes to the broader goal of building a harmonious plural society in Indonesia.